Job ladder and business cycles - Felipe Alves (Bank of Canada, 2022)
I build a Heterogeneous Agents New Keynesian model with rich labor market dynamics. Workers search both off- and on-the-job, giving rise to a job ladder, where employed workers slowly move toward more productive and better paying jobs through job-to-job transitions, while negative shocks occasionally throw them back into unemployment. The state of the economy includes the distribution of workers over wealth, labor earnings and match productivities. In the wake of an adverse financial shock calibrated to mimic the US Great Recession unemployment dynamics, firms reduce hiring, causing the job ladder to all but "stop working." This leaves wages stagnant for several years, triggering a sharp contraction and slow recovery in consumption and output. On the supply side, the slow pace in worker turnover leaves workers stuck at the bottom of the ladder, effectively cutting labor productivity growth in the aggregate. The interaction between weak demand and low productivity leads to inflation dynamics that resemble the missing disinflation of that period.
Keywords: D31; D52; E21; E24; E31; E32; 330; Business fluctuations and cycles; Labour markets; Productivity; Inflation and prices